Are we feeling happy now? - James F. O'Callaghan (Revista Espaço Acadêmico, 2021)
When asked, “What is happiness?,” a philosopher like St. Augustine responds with an entire worldview. We’re more comfortable with the man who shrugs and says, “Hey, if you have to ask you wouldn’t understand.” With him we think we know, pretty much, what it means to be happy. Invoking God and human nature and all that makes us impatient and uncomfortable and, well, unhappy. The trick is not to ask questions but just to be happy with never a philosophical thought. But there’s sort of a Catch-22 involved. In pursuing the things we need or want in education or work, in relationships or social issues, we bump up against questions of the good life and the bad life, of duty and justice and more. When we try to fall asleep we discover we have become philosophers and theologians, mulling over gloomy thoughts of death and destiny.